The Effects of Long-Term Storage on the Quality of Palm Oil Biodiesel and Canola Oil Biodiesel - Yoyon Wahyono; Hadiyanto Hadiyanto; Mochamad Arief Budihardjo; Rifqi Ahmad Baihaqi; Ainun Nurusy Syahida (Journal of Engineering and Technological Sciences, 2022)
Effective storage of biodiesel has proven to be a challenge, which the Indonesian government has invested billions of Indonesian rupiahs (IDR) in to overcome. It is thus important to investigate how different storage methods can affect the quality of biodiesel. The purpose of this study was to determine how storage at room temperature in the dark affects the quality of palm oil biodiesel (POB) and canola oil biodiesel (COB). POB and COB were stored in closed containers at 22 °C in the dark for 12 months. The results showed that POB was more significantly damaged than COB. This study found increases of density (POB by 51.52 kg/m3 and COB by 17.52 kg/m3), kinematic viscosity (POB by 0.67 mm2/s and COB by 0.32 mm2/s), acid value (POB by 0.27 mg-KOH/g and COB by 0.25 mg-KOH/g), total glycerol (POB by 0.58%-mass and COB by 0.60%-mass), and peroxide value (POB by 48 meq-O2/kg and COB by 54 meq-O2/kg), whereas there were decreases in fatty acid methyl esters (POB by 7.11%-mass and COB by 9.36%-mass). Gas chromatography-mass spectrometry results for POB and COB showed decreases in 9-octadecenoic acid methyl ester and 9,12-octadecadienoic acid (Z,Z)-methyl ester, and increases in 9-octadecenoic acid and 9,12-octadecadienoic acid (Z,Z). Fourier transform infrared spectroscopy (FTIR) results revealed the presence of methyl ester functional groups. The storage of biodiesel in a closed container at 22 °C in the dark can minimize biodiesel oxidation, as evidenced by the findings of this study, namely, the insignificant formation of ketone and aldehyde groups in the biodiesel oxidation process during storage, based on the results of FTIR.